2012
DOI: 10.5006/i0010-9312-68-6-507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the Grain Size Dependence of Magnesium Corrosion

Abstract: Prior works show that grain size can play a role in the corrosion of a metal; however, such works are nominally executed in a single electrolyte/environment at a single pH. In this work, the anodic and cathodic reaction kinetics of pure Mg specimens with grain sizes ranging from approximately 8 μm to 590 μm were compared as a function of pH in 0.1 mol dm -3 sodium chloride (NaCl) electrolytes using anodic polarization experiments and an in situ scanning vibrating electrode technique (SVET). Anodic polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…The formation of discs versus filaments was suggested to depend on whether the catalytic efficiency of the locally corroded region allowed for galvanic coupling with its perimeter, or merely along the most anodic pathways of the microstructure. 7 This "differential electrocatalytic" mechanism was also shown to drive filiform corrosion on coated Mg as determined by scanning Kelvin probe (SKP) measurements. 1 The mechanism, however, by which the cathodic reaction (H 2 gas evolution) is enhanced on corroded Mg or Mg alloys continues to be unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of discs versus filaments was suggested to depend on whether the catalytic efficiency of the locally corroded region allowed for galvanic coupling with its perimeter, or merely along the most anodic pathways of the microstructure. 7 This "differential electrocatalytic" mechanism was also shown to drive filiform corrosion on coated Mg as determined by scanning Kelvin probe (SKP) measurements. 1 The mechanism, however, by which the cathodic reaction (H 2 gas evolution) is enhanced on corroded Mg or Mg alloys continues to be unclear.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Williams et al have offered critical insights into the electrochemical mechanism of this unique localized corrosion mode on pure Mg 1,5,7 and the Mg-Al-Zn-Mn alloy AZ31B 9 by employing the scanning vibrating electrode technique (SVET), where their SVET measurements showed that the corrosion filaments/discs became cathodically-activated following their formation. It was proposed that the net cathode on the locally corroded regions galvanically coupled with the adjacent intensely anodic regions to drive the lateral propagation of the corrosion products across the exposed surface.…”
mentioning
confidence: 99%
“…Mg and Mg alloys have been shown to be susceptible to the formation of laterally-spreading corrosion products, which tend to form thread-like "filaments" or radially-expanding "discs" in neutral-pH sodium chloride (NaCl) solutions with concentrations ranging from 0.01 M to 0.86 M. [1][2][3][4][5][6][7][8][9][10][11][12] Williams et al have employed the scanning Kelvin probe (SKP) 1 and the scanning vibrating electrode technique (SVET) 1,5,9 to show that this behavior is driven by a "differential electrocatalytic" mechanism, whereby areas consumed by the corrosion products catalyze the cathodic hydrogen evolution (HE) reaction. The HE reaction has been proposed to be catalyzed by non-alloyspecific mechanisms including undissolved metallic Mg "chunks" and a significantly roughened surface film, 5,13 in addition to alloyspecific mechanisms including enrichment of noble (relative to Mg) alloy constituents.…”
mentioning
confidence: 99%
“…It has been found that the propagation of filaments occurs with voluminous gas evolution at the head while the body immediately behind it passivates [62]. Filiform corrosion has been observed in high purity magnesium of unpolarised and galvanostatically polarised specimen in aqueous sodium chloride electrolyte [52,56]. A relatively widespread surface coverage of what is the typically observed filiform-like corrosion morphology [63] was observed for pure Mg.…”
Section: Global and Local Electrochemical Behaviour Of Az91 In 01 M mentioning
confidence: 82%
“…The presence of this resistant surface film was revealed by EDS measurements. Filiform corrosion has previously been observed in pure magnesium [13,[49][50][51][52][53][54][55][56] as well as Mg-Al [57,58], Mg-Y [50], Mg8Li [55], AM30 [59], AZ31 [60,61], AZ80 [60], AZ91D [13] and AZ91 [51] alloys after immersion in chloride-containing solutions. It has been found that the propagation of filaments occurs with voluminous gas evolution at the head while the body immediately behind it passivates [62].…”
Section: Global and Local Electrochemical Behaviour Of Az91 In 01 M mentioning
confidence: 99%